Proposta de arranjo para gestão dos recursos hídricos na comunidade Parque São Pedro, Manaus- Am. - Pinto, Luciani Aguiar (2018)
Based on Law 9.433 / 97, which instituted the National Water Resources Policy (PNRH), the State of Amazonas created its water management policy and the State System for Water Resources Management (SEGREH), through Law 2.712 / 2001, restated by Law 3.167 / 2007. However, after 17 years, the SEGREH presents low effectiveness, with precarious development of the committees of state basins and slow implementation of the management instruments. On the other hand, urban rivers and streams are in an accelerated process of degradation. This scenario is further aggravated by the unfavorable social participation in the management of water resources, as recommended by the PNRH. In this sense, this study aimed to propose a model of community arrangement for water management, with the object of study being the urban community Parque São Pedro, in Manaus, capital of Amazonas, in order to stimulate and strengthen social participation in the management of waters. With this purpose, the study was developed starting with the survey of the legal instruments related to water management, perception of the way the SEGREH works, as well as the community characterization, which allowed to identify the impacts on water bodies and local agents. The result pointed to the elaboration of a model of local arrangement, based on the degree of relationship of the agents with the community, where the organizations with greater interest in the general improvement of the community are more involved in the arrangement and consequently must be more effective in the SEGREH. The proposal brings a differentiated form of participation of the society, because it was concerned with the direct involvement of the local agents and not only with the representation by segment. At the same time, it sought to involve all local segments: civil society, public power and users. In addition, the model presents flexibility, allowing self-assessment and self-tuning of the arrangement, and points out some strengths and weaknesses that should guide a possible implementation. It is believed that the proposal will allow approximation and consequent community participation in the water resources system, giving voice to local problems, contributing to the improvement and / or adequacy of the state system of water resources management.